Post-traumatic responses to workplace violence among nursing professionals: a collaborative and comparative study in South Korea and Hong Kong - Soyun Hong; Sujin Nam; Janet Yuen Ha Wong; Heejung Kim (BMC, 2023)
Abstract Background Workplace violence has had a significant and negative psychological impact on nursing professionals worldwide. Concerted worldwide efforts to improve work environments have not yet removed nursing professionals from the threat of violence. It is highly essential to conduct comparative research in various working environments where the nurses of each country have unique experiences of workplace violence. The aim of this study was to examine the differences in the rate, associated factors, and post-traumatic responses to workplace violence between South Korean and Chinese nurses in Hong Kong among East Asian countries. Methods A cross-sectional, correlational study design recruited a total of 471 registered nurses (319 South Korean nurses and 152 Chinese nurses in Hong Kong; overall response rate = 78.5%) at online communities in South Korea and Hong Kong. The data were collected by conducting a Qualtrics survey from January 15, 2020, to July 24, 2021. A structured questionnaire was administered for data collection, including rate of workplace violence, perception of workplace violence, attitudes toward workplace violence, coping styles, post-traumatic cognitions, post-traumatic stress disorder, post-traumatic growth, and mental health indicators (depression, anxiety, and stress). T-test, chi-squared, and binary logistic regression analyses were conducted. Results In our sample, 30.7% South Korean nurses and 31.6% Chinese nurses in Hong Kong had experienced workplace violence. South Korean and Chinese nurses in Hong Kong with experience of workplace violence had lower perceptions of it. Nurses with experience of workplace violence reported lower levels of mental health, and this trend was more prominent among South Korean nurses. Conclusions Our study findings showed a positive association between workplace violence and post-traumatic responses in both settings. We found that the close monitoring of post-traumatic responses associated with workplace violence could be improved by enhancing nurses' perception of workplace violence.